Comparison the Impact of the Metformin and Insulin on Different Biochemical Markers in Type II Diabetes Mellitus - Majid Hameed Almousawy, Ferdous Abbas Jabir, (Pakistan Journal of Medical & Health Sciences, 2022)
T2DM was called a non-insulin dependent type. The cause is either insulin resistance with insulin insufficiency or from defect in insulin secretion combined with insulin resistance. It usually occurs before 40 years old age, but also can occur at less than that age. About 50% of male and 70% of female cases often are obese. The management of diabetes has been practiced since the Middle Ages with several treatments. The first treatment called metformin is a biguanide drug that is usually used as the first-line oral treatment for T2DM in people of all ages. The second treatment used is insulin therapy (with or without additional medications) that should be started in newly diagnosed T2DM patients with symptoms (catabolic characteristics such as weight loss, ketosis, or signs associated with hyperglycemia such as frequent urination/polydipsia) and/or have a severe increase in blood sugar levels. Results: In type II diabetic patients who treated with compare of metformin or insulin The results was indicated a significant difference parameters in duration of treatment and blood glucose , as well as , there was a strong positive correlation between ALT and AST in in treated with metformin or insulin. Conclusions: In type II diabetic patients, metformin or insulin treatments have the same effect on the activities of ALT, AST, SOD, GST and lipid profile , except for the level of glucose depending on the disease severity, study the correlation of ALT and AST activities with some biochemical markers in type 2 diabetic patients treated with metformin and insulin.